Role of multidrug-resistance protein 2 in coproporphyrin transport: Results from experimental studies in bile fistula rat models - Moriondo, V; Marchini, S; Di Gangi, P; Ferrari, M C; Nascimbeni, F; Rocchi, E; Ventura , P (Cellular and Molecular Biology, 2009)
Coproporphyrin (CP) is one of the main by-products of heme biosynthesis and its abnormal accumulation is associated with different forms of porphyria. Indirect data obtained from animal and human models have suggested a possible role for Multidrug Resistance-associated Protein 2 (MRP2) and other MRPs in hepatocyte excretion of CP. Using normal, MRP2-deficient and a cholestatic rat model, we have assessed the role of MRPs in CP disposition. MRP levels were assayed using immunofluorescence. Biliary and urinary excretion patterns of CP and conjugate bilirubin were measured during equimolar infusions of CP isomers with and without phenoldibromopthalein sulfonate (BSP), a well-known MRP2 substrate. Our results suggest a role for the MRP system as a possible regulator of CP traffic and accumulation in normal and pathological conditions. Alteration in this systems (as observed in cholestatic disease) may play an important role in triggering clinical expression of porphyria in individuals with underlying mutations leading to porphyrin accumulation and may help explain the phenotypic heterogeneity in patients affected by different forms of porphyrias.